Crimean–Congo Hemorrhagic Fever Virus and Borrelia burgdorferi sensu lato in Ticks from Kosovo and Albania - Sherifi, Kurtesh; Rexhepi, Agim; Berxholi, Kristaq; Mehmedi, Blerta; Gecaj, Rreze M.; Hoxha, Zamira; Joachim, Anja; Duscher, Georg G. (Frontiers in Veterinary Science, 2018)
Tick-borne diseases pose a serious threat to human health in South-Eastern Europe, including Kosovo. While Crimean-Congo hemorrhagic fever (CCHF) is a well-known emerging infection in this area, there are no accurate data on Lyme borreliosis and tick-borne encephalitis (TBE). Therefore we sampled and tested 795 ticks. Ixodes ricinus (n=218), Dermacentor marginatus (n=98) and Haemaphysalis spp. (n=24) were collected from the environment by flagging (all from Kosovo), while Hyalomma marginatum (n=199 from Kosovo, all from Kosovo) and Rhipicephalus bursa (n=130, 126 from Albania) could be collected only by removal from animal pasture and domestic ruminants. Ticks were collected in the years 2014/2015 and tested for viral RNA of CCHF and TBE viruses, as well as for DNA of Borrelia burgdorferi sensu lato by real-time PCR. In Kosovo nine ticks were positive for RNA of CCHFV and seven for DNA of Borrelia burgdorferi s. l. None of the ticks tested positive for TBEV. CCHF virus was detected in one H. marginatum male specimen collected while feeding on grazing cattle from the Prizren region and in eight R. bursa specimens (five females and three males collected while feeding on grazing sheep and cattle) from the Prishtina region (Kosovo). B. burgdorferi s. l. was detected in seven questing ticks (four male and one female D. marginatus, two I. ricinus one female and one male) from the Mitrovica region (Kosovo). Our study confirmed that CCHF virus is circulating in Kosovo mainly in H. marginatum and R. bursa in the central areas of the country. B. burgdorferi s. l. was found in its major European host tick, I. ricinus, but also in D. marginatus, in the north of the Kosovo. In order to prevent the spread of these diseases and better control of the tick-borne infections an improved vector surveillance and testing of ticks for the presence of pathogens needs to be established.